Children's school theatre between production norms and writing objectives: Reading in selected samples - Rouigui, Rebaia; Kadid, Diab (Journal of Human Sciences, 2023)
This study aims at identifying the central role occupied by the Theatre in Education (TIE), as well as its pedagogical, educational contributions to the development of the child's personality at the intillectual, social, psychological and scientific levels. This very aim can be achieved through the exploration of TIE's precise definitions, in addition to framing the relationship between the school and the learner in the TIE. We, then, carefully studied and examined a selection of Child-entred plays in view to outline the study's final findings which are the key criteria set for producing education-related texts. These criteria led to the fact that the TIE is one of the most effective tools to conduct a successful educational process, and to serve the pedagogical system. This is the case because the TIE accomplishes the pedagogical, educational objectives on the one hand; and developing the child's personality in view to advance their intillectual and cognitive abilities on the other hand, alongside entertainment and leisure.